2021
DOI: 10.33474/j.sa.v3i2.8100
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Skrining Fitokimia dan Aktivitas Antioksidan Ekstrakk Biji Sangrai Kopi Robusta (Coffea canephora) dari Tanaman Hasil Pemupukan Organik dan Anorganik

Abstract: Ground coffee is coffee beans that have been roasted, ground or ground so that they have a smooth shape. The purpose of this study was to determine the content of compounds in robusta coffee roasted seed extract (Coffea canephora) from plants produced by organic and inorganic fertilization, and to know the difference in compounds between the results of organic and inorganic fertilization. The characteristics of phytochemical screening were carried out qualitatively on alkaloids, flavonoids, tannins, terpenoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…In general, robusta coffee originating from West Lampung contains various phytochemical compounds such as caffeine, flavonoid, alkaloid, tannin, and saponin in line with study conducted by (Wigati et al 2019) where extract from robusta coffee beans cultivated in Bandung, Bogor, and Garut, West Java contained alkaloids, flavonoids, saponins, and tannins, the same as Robusta coffee grown in Central Java (Temanggung, Boyolali, Wonosobo) and East Java (Jombang, Malang, and Kediri) (Utami et al 2018). Furthermore, the results of the phytochemical characteristic test showed that the robusta coffee seed extract obtained from Malang, East Java contains flavonoids, alkaloids, terpenoids, tannins, and saponins (Nada et al 2021). The crude methanolic extracts of…”
Section: Discussionmentioning
confidence: 99%
“…In general, robusta coffee originating from West Lampung contains various phytochemical compounds such as caffeine, flavonoid, alkaloid, tannin, and saponin in line with study conducted by (Wigati et al 2019) where extract from robusta coffee beans cultivated in Bandung, Bogor, and Garut, West Java contained alkaloids, flavonoids, saponins, and tannins, the same as Robusta coffee grown in Central Java (Temanggung, Boyolali, Wonosobo) and East Java (Jombang, Malang, and Kediri) (Utami et al 2018). Furthermore, the results of the phytochemical characteristic test showed that the robusta coffee seed extract obtained from Malang, East Java contains flavonoids, alkaloids, terpenoids, tannins, and saponins (Nada et al 2021). The crude methanolic extracts of…”
Section: Discussionmentioning
confidence: 99%
“…Pada uji flavonoid ditujukan dengan terbentuknya warna jingga saat ekstrak direaksikan dengan logam Mg dan HCl sehingga terbentuk gelembunggelumbung yang merupakan gas H2. Adanya flavonoid ditandai dengan perubahan warna jingga, merah bata, merah muda, dan merah tua [23]. Pada uji terpenoid dan steroid terjadi perubahan warna menjadi warna hijau pekat.…”
Section: Keteranganunclassified
“…Pada pengujian saponin dinyatakan mendapatkan hasil positif, hal ini dikarenakan saponin dalam ekstrak ditandai dengan terbentuknya busa setelah pengocokan terhadap ekstrak yang dilarutkan dalam air panas. Umumnya, senyawa saponin berada dalam bentuk glikosida sehingga memiliki kemampuan membentuk buih dan air [23]. Busa yang dihasilkan terbentuk dari reaksi antara gugus hidrofobik dengan udara.…”
Section: Keteranganunclassified